Electron Spectrum and Tunneling Current of the Toroidal and Helical Graphene Nanoribbon-Quantum Dots Contact. (25th April 2011) - Belonenko, Mikhail B.; Lebedev, Nikolay G.; Zhukov, Alexander V.; Yanyushkina, Natalia N.
Abstract : We study the electron spectrum and the density of states of long-wave electrons in the curved graphene nanoribbon based on the Dirac equation in a curved space-time. The current-voltage characteristics for the contact of nanoribbon-quantum dot have been revealed. We also analyze the dependence of the specimen properties on its geometry.